Robust Density of Periodic Orbits for Skew Products with High Dimensional Fiber - Fatemeh Helen Ghane; Mahboubeh Nazari; Mohsen Saleh; Zahra Shabani (Abstract and Applied Analysis)
We consider step and soft skew products over the Bernoulli shift which have an -dimensional closed manifold as a fiber. It is assumed that the fiber maps Hölder continuously depend on a point in the base. We prove that, in the space of skew product maps with this property, there exists an open domain such that maps from this open domain have dense sets of periodic points that are attracting and repelling along the fiber. Moreover, robust properties of invariant sets of diffeomorphisms, including the coexistence of dense sets of periodic points with different indices, are obtained.